Philosophical Theories of Truth and Nursing: Exploring the Tensions. (January 2019) - Thoun, Deborah S.; Kirk, Megan; Sangster-Gormley, Esther; Young, James O.
In this paper, the authors explore three philosophical theories of truth and offer a critique of this foundational area of scholarship for nursing. A brief summary of key ideas related to the three substantial philosophical theories of truth—that is, correspondence, pragmatism, and coherence—serves to highlight various convictions and commitments that facilitate or discourage the growth of nursing knowledge in particular ways. The authors conclude that the coherence theory of truth offers a more inclusive view of truth and best captures and supports the diversity that exists within nursing knowledge and the regulative ideal to which nursing aspires.